Bioplastic from Pectin of Dragon Fruit (Hylocereus polyrhizus) Peel - Risnita Vicky Listyarini; Puspita Ratna Susilawati; Esther Natalia Nukung; Maria Anastasia Toyo Yua (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Plastic derived from petroleum is challenging to degrade and pollute the environment. There are alternatives to making biodegradable plastics to reduce the adverse effects of plastics on the environment. This study aims to utilize dragon fruit peel waste as a material for making bioplastic. Plastic characterization was carried out by FTIR analysis to determine the functional groups contained in bioplastics. The results showed that dragon fruit peel could be extracted by HCl solution, and the pectin yield is 11%. Extracted pectin was used to make bioplastics with and without the addition of ethylene glycol. The results showed that moisture content of bioplastics of dragon fruit peel pectin is 5.71–12%, while dragon fruit peel pectin and ethylene glycol are 2.86–5.71%. FT-IR spectra showed that the bioplastics from dragon fruit peels belong to the pectin group, which produces carbonyl absorption at 1636–1628 cm-1 and stretching C-O stretch at 1098–1101 cm‑1.